2007
DOI: 10.1002/jmv.20862
|View full text |Cite
|
Sign up to set email alerts
|

Human caliciviruses in symptomatic and asymptomatic infections in children in Vellore, South India

Abstract: Pediatric gastroenteritis is a major cause of childhood morbidity and mortality worldwide, especially in developing countries. It has been increasingly recognised that human caliciviruses (HuCV), comprising noroviruses (NoV), and sapoviruses (SaV), are important in both outbreak and non-outbreak settings. This study aimed to characterise caliciviruses detected in the faeces of hospitalized children and children in the community in India. This study examined 350 faecal samples from children presenting to the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
71
3
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 34 publications
18
71
3
2
Order By: Relevance
“…Hospital-based studies from India between 2003 and 2009 reported a 6% prevalence of NoV associated diarrhea among children 5 years of age, [21][22][23][24] which is lower than the current study. This variation could be a result of the detection method used.…”
Section: Discussioncontrasting
confidence: 89%
“…Hospital-based studies from India between 2003 and 2009 reported a 6% prevalence of NoV associated diarrhea among children 5 years of age, [21][22][23][24] which is lower than the current study. This variation could be a result of the detection method used.…”
Section: Discussioncontrasting
confidence: 89%
“…This is due to norovirus causing less severe diarrhoea than rotavirus and parents tend not to seek medical services [25,26]. In our study, the severity of diarrhoea episodes was similar in children with and without NoV and similar high detection rates had been reported from Chile, India and Nicaragua at that time when the vaccines had not been introduced [18][19][20].…”
Section: Discussionsupporting
confidence: 81%
“…Globally, hospital-based series in children with diarrhoea report a median of 14%, which seems lower than the proportions detected in our study [17]. Although our data suggests an annual increase in the proportion of cases, similar detection rates had been reported from Chile, India and Nicaragua prior to rotavirus vaccine introduction [18][19][20]. This relative increase may also be due to the decrease of number of rotavirus-related hospitalizations [10,11] and all-cause diarrhoea cases due to the effectiveness of the rotavirus vaccine [21] and the herd effect of the vaccine that has resulted in an overall and not a real increase in the overall number of NoV cases.…”
Section: Discussioncontrasting
confidence: 49%
“…5·1-12·7% of cases hospitalized with AG [11,18,19]. In the present study, SaV was detected in 2·7% of children with AG and in 1·9% of asymptomatic children.…”
Section: Discussionsupporting
confidence: 49%